Establishing standard working procedures to investigate effects of channa striatus bloch crude extract on malassezia furfur growth - Far, Fatemeh Ehtesham (2012)
Skin fungal infections are a common type of skin diseases that has become a global problem. Fungal infections commonly constitute a health problem in developing countries particularly in tropical and subtropical regions. Malassezia and Candida species are the most prevalent pathogens in human and animals. Yeast-like fungus Malassezia furfur is associated with several dermatological diseases such as Pityriasis versicolor, Malassezia folliculitis, Atopic dermatitis and Seborrheic dermatitis (Dandruff). The available drugs known as antimycotic act against extensive range of molecular targets of fungi but the numbers of antifungal resistance pathogens have increased. Furthermore, majority of these antifungal drugs are synthetic that lead to some health-threatening side-effects. Consequently, increasing demand for seeking the natural therapeutic medicines has made much attention to pelagic organisms, especially, fish that can be found throughout the ocean. There are no standard parameters for minimum fungicidal concentration (MFC), as well as definitive guideline for evaluating the antifungal drugs against Malassezia species. So, this study attempted to apply some modified methods which are more adjustable for M. furfur in order to perform antifungal susceptibility tests. Therefore, this research was planned to evaluate effects of Channa striatus crude extract on yeastlike fungi M. furfur ATCC 14521 through bioassays. Bioassay studies demonstrated that Channa striatus crude extract in various concentrations did not show inhibitory activity against M. furfur which was evidenced in terms of minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC) tests and percentage of cell viability using colorimetric assay. Besides, colorimetric resazurin microtitre assay (REMA) Plate Method expressed Channa striatus crude extract to have proliferative effect on M. furfur in comparison with growth control. As a conclusion, it was previously hypothesized that possibly Channa striatus crude extract has sufficient antifungal properties to inhibit M. furfur growth. But, based on the in vitro data of this study, Channa striatus crude extract exacerbate the diseases associated with M. furfur. Therefore, it cannot be an effective natural antimycotic medicine to treat skin diseases related to M. furfur.